HCI in business : First International Conference, HCIB 2014, Held as Part of HCI International 2014, Heraklion, Crete, Greece, June 22-27, 2014. Proceedings - Nah, Fiona Fui-Hoon (Lecture Notes in Computer Science, 2014)
This volume constitutes the refereed proceedings of the First International Conference on HCI in Business, HCIB 2014, held as part of the 16th International Conference on Human-Computer Interaction, HCI International 2014, in Heraklion, Crete, Greece, jointly with 13 other thematically similar conferences. The total of 1476 papers and 220 posters presented at the HCII 2014 conferences was carefully reviewed and selected from numerous submissions. The papers address the latest research and development efforts and highlight the human aspects of design and use of computing systems. They thoroughly cover the entire field of human-computer interaction, addressing major advances in knowledge and effective use of computers in a variety of application areas. The 76 papers included in this volume deal with the following topics: enterprise systems; social media for business; mobile and ubiquitous commerce; gamification in business; B2B, B2C, C2C e-commerce; supporting collaboration, business and innovation and user experience in shopping and business.